Assessment of body fluid balance and voluntary drinking in ultimate players during a match - Martarelli, D.; Uguccioni, F.; Stauffacher, S.; Spataro, A.; Cocchioni, M.; Pompei, P. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM. Ultimate is a sport played by hundreds of thousands of people in more than 42 countries; however, it is still mainly known as a recreational more than a team sport, and further studies are needed to define its physical load. Particularly, since no studies relating Ultimate to hydration have been performed, we aimed to determine body fluid balance, voluntary water intake and the most reliable method for assessing the hydration status of players after a typical 80-minute Ultimate match. METHODS: bioimpedance, urine specific gravity and body mass changes to asses the hydration level of the players were measured. RESULTS: It was observed that not all of the methods are adequate to determine dehydration in Ultimate players, and that measurement of body mass changes represents a reliable and accurate technique. CONCLUSIONS: These findings demonstrate that ultimate as an intense sport that can induce significant fluid loss, which is not always replaced by individual drinking.